Implementation of Education Digitalization Policy in Central Kalimantan: IFP/Smart Board Utilization Readiness in Pulang Pisau Senior High Schools - Toto Pujiharyanto (Politeia : Journal of Public Administration and Political Science and International Relations, 2026)
This article maps implementation readiness for the education digitalization policy in Central Kalimantan Province through the use of Interactive Flat Panels (IFPs)/smart boards at senior high schools in Pulang Pisau Regency. Using an integrated lens (Edwards III + TAM + TPACK), the study distinguishes between “devices being available” and “devices being used meaningfully” by examining governance arrangements, infrastructure conditions, and pedagogical integration. A multi-site case study across nine schools (eight subdistricts) combined a review of policies/documents, administrative facility profiles (Kemendikdasmen Education Data), and a descriptive survey of school-level implementers (n = 25). The analysis shows that the use of IFPs/smart boards has the potential to strengthen interactive learning and support the Merdeka Curriculum. A consistent pattern was frequent and positively perceived use: 73.3% of respondents reported using IFPs at least five times per week, most commonly for collaborative projects (40.0%) and presentations (33.3%), while 80.0% reported using interactive features in more than 50% of sessions. Nevertheless, readiness varies according to operational conditions and governance, particularly reliance on personal hotspots when connectivity is limited (53.3%), uneven consistency in SOP implementation (20.0% reported written SOPs that were not implemented consistently; 13.3% reported relying only on informal SOPs), and technical-support arrangements (only 40.0% reported formal reporting channels with rapid responses and/or service-time targets). This study does not measure classroom learning outcomes; rather, it reports readiness and governance conditions that shape routine use. A feasible minimum implementation package should prioritize: (1) standardized SOPs for use, access, and asset governance; (2) sustained TPACK-oriented mentoring; and (3) tiered maintenance/helpdesk arrangements and utilization monitoring focused on usage indicators rather than procurement.